Building a Culture of Peace in Education: An Exploration of Al-Ghazali's Thoughts on Inner and Social Peace - Andi Wahyu Irawan; M. Solehuddin; Ilfiandra Ilfiandra; Hani Yulindrasari (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
A culture of peace in education is a concept that emphasizes the importance of creating a harmonious learning environment and respecting differences to achieve an effective, conducive, and harmonious learning environment for students. Research on the culture of peace in education on the mental and social aspects of creating peace often receives less attention. The thoughts of figures such as Imam Al-Ghazali offer a holistic and comprehensive view of peace. This study aimed to explore Imam Al-Ghazali's thoughts on inner and social peace and how to build a culture of peace in education. A qualitative approach was chosen to understand Imam Al-Ghazali's thoughts on inner and social peace and how these concepts can be applied in an educational context. The methods used in this research were literature study and content analysis. The three main works of Imam Al-Ghazali studied were Ihya 'Ulum al-Din, Al-Munqidh min al-Dalal, and Bidayat al-Hidayah. The results showed three principles in building a culture of peace: inner peace, cleansing of the soul, and noble character. This study has an implication to pay attention to mental and social aspects of creating a harmonious learning environment by strengthening the values of tolerance, empathy, justice, cooperation, and peaceful conflict resolution in the curriculum and learning. In addition, the character building of students who can communicate, think critically, and solve problems peacefully should be prioritized in education.